Effects of long-term PM 2.5 exposure on metabolic syndrome among adults and elderly in Guangdong, China - Xue-yan Zheng; Si-li Tang; Tao Liu; Ye Wang; Xiao-jun Xu; Ni Xiao; Chuan Li; Yan-jun Xu; Zhao-xuan He; Shu-li Ma; Yu-liang Chen; Rui-lin Meng; et al. (BMC, 2022)
Abstract Background We aimed to explore the association between long-term exposure to particulate matter ≤ 2.5 µm (PM2.5) and metabolic syndrome (MetS) and its components including fasting blood glucose (FBG), blood pressure, triglyceride (TG), high-density lipoprotein cholesterol (HDL-c) and waist circumference among adults and elderly in south China. Methods We surveyed 6628 participants in the chronic disease and risk factors surveillance conducted in 14 districts of Guangdong province in 2015. MetS was defined based on the recommendation by the Joint Interim Societies' criteria. We used the spatiotemporal land-use regression (LUR) model to estimate the two-year average exposure of ambient air pollutants (PM2.5, PM10, SO2, NO2, and O3) at individual levels. We recorded other covariates by using a structured questionnaire. Generalized linear mixed model was used for analysis. Results A 10-μg/m3 increase in the two-year mean PM2.5 exposure was associated with a higher risk of developing MetS [odd ratio (OR): 1.17, 95% confidence interval (CI): 1.01, 1.35], increased risk of fasting blood glucose level. (OR: 1.18, 95% CI: 1.02, 1.36), and hypertriglyceridemia (OR: 1.36, 95% CI: 1.18, 1.58) in the adjusted/unadjusted models (all P < 0.05). We found significant interaction between PM2.5 and the region, exercise on the high TG levels, and an interaction with the region, age, exercise and grain consumption on FBG (P interaction < 0.05). Conclusions Long-term exposure to PM2.5 was associated with MetS, dyslipidemia and FBG impairment. Efforts should be made for environment improvement to reduce the burden of MetS-associated non-communicable disease.